2013
DOI: 10.1210/en.2012-2070
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a Plays an Important Role in Cell Cycle Regulation in ACTH-Secreting Pituitary Adenomas by Modulating Protein Kinase Cδ

Abstract: The functional aftermath of microRNA (miRNA) dysregulation in ACTH-secreting pituitary adenomas has not been demonstrated. miRNAs represent diagnostic and prognostic biomarkers as well as putative therapeutic targets; their investigation may shed light on the mechanisms that underpin pituitary adenoma development and progression. Drugs interacting with such pathways may help in achieving disease control also in the settings of ACTH-secreting pituitary adenomas. We investigated the expression of 10 miRNAs among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 52 publications
2
35
0
3
Order By: Relevance
“…However, although technical limitations precluded us from determining the relative or absolute contribution of each of these pathways, our conclusions are reinforced by the independent approaches that reach similar conclusions and described above. [11,14,45] Thus far, investigations characterizing the inappropriate expression of miRNA in the genesis of pituitary adenomas has already led to the identification of subtype-specific miRNA profiles [46,47,16], identification of miRNA that show correlations with tumour size [40] or are predictive of tumor sensitivity and or response to therapeutic interventions. [47,16] and have been subject to recent and extensive review, [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although technical limitations precluded us from determining the relative or absolute contribution of each of these pathways, our conclusions are reinforced by the independent approaches that reach similar conclusions and described above. [11,14,45] Thus far, investigations characterizing the inappropriate expression of miRNA in the genesis of pituitary adenomas has already led to the identification of subtype-specific miRNA profiles [46,47,16], identification of miRNA that show correlations with tumour size [40] or are predictive of tumor sensitivity and or response to therapeutic interventions. [47,16] and have been subject to recent and extensive review, [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, and in this context, some of these issues have been subject to recent review (52). More recent reports that in this case identify targets of miRNA that themselves play key roles or are central regulators of pathways that include, as example protein kinase Cδ and PTEN-AKT respectively might offer alternate indirect approaches [16,15]. In these cases investigators identified previously unknown, but what would appear to be novel targets that may represent pathways for more direct therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell line was maintained in DMEM (Invitrogen) supplemented with 10% horse serum (HS) (LGC Standards, Milano, Italy) and antibiotic antimycotic (EuroClone, Milano, Italy) at 37 8C in 5% CO 2 , as described previously (Gentilin et al 2013). Before each experiment, cells were incubated in 0.5% HS medium for 48 h followed by a 24-h incubation in 10% HS medium.…”
Section: Cell Culturementioning
confidence: 99%
“…Egy miRNS-nek a bá-zispárosodás szabályai szerint több célgénje is van, és egy célmolekula kifejeződését számos miRNS is szabályoz-hatja. A biológiai funkciók hátterében álló mechanizmusokat a sejten belüli jelátviteli útvonalakkal lehet a leginkább jellemezni, így a miRNS-ek szabályozó szerepét nemcsak egy-egy génhez (1. táblázat) [34,42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], hanem egy-egy jelátviteli útvonalhoz is lehet rendelni.…”
Section: A Mirns-ek áLtal éRintett Jelátviteli úTvonalak Az Agyalapimunclassified